Anatomical Variation of the Maxillary Sinus in Cone Beam Computed Tomography - Marcelo Lupion Poleti; Luciana Maria Paes da Silva Ramos Fernandes; Christiano Oliveira-Santos; Ana Lúcia Alvares Capelozza; Luiz Eduardo Montenegro Chinellato; Izabel Regina Fischer Rubira-Bullen (Hindawi Limited, 2014)
Purpose. The aim of this paper is to report a case in which the cone beam computed tomography (CBCT) was important for the confirmation of the presence of maxillary sinus septum and, therefore, the absence of a suspected pathologic process. Case Description. A 27-year-old male patient was referred for the assessment of a panoramic radiograph displaying a radiolucent area with radiopaque border located in the apical region of the left upper premolars. The provisional diagnosis was either anatomical variation of the maxillary sinuses or a bony lesion. Conclusion. The CBCT was important for an accurate assessment and further confirmation of the presence of maxillary septum, avoiding unnecessary surgical explorations.